Management of green mould (Trichoderma viride) in button mushroom (Agaricus bisporus) - Pathania, Akshay; Jarial, Rajender Singh; Jarial, Kumud; Dhiman, Riya (Mushroom Research, 2025)
Green mould is a highly destructive affliction that plagues button mushroom cultivation, resulting in substantial annual losses. This study focused on evaluating the effectiveness of diverse fungicides and botanicals for its mitigation. Seven fungicides and eight botanicals were subjected to rigorous testing against Trichoderma viride and Agaricus bisporus mycelium. Result revealed that under in vitro conditions, Bavistin, Tilt and Contaf fungicides showed maximum inhibition (100%) against T. viride Whereas, among tested botanicals, Allium sativum exhibited a maximum (72.51%) inhibition of T. viride mycelium followed by Curcuma longa (56.33%) displayed significant efficacy against T. viride. Further assessments under natural hut conditions included in vivo trials with four botanicals (Tagetes sp., Allium sativum, Azadirachta indica, Justicia adhatoda) and one fungicide (Bavistin) alongside positive and negative controls concluded that Tagetes sp. and Bavistin significantly increased mushroom yield compared to the negative control infected with the green mould pathogen. In a commercial production setting, the application of Justicia adhatoda leaf extract on bags yielded minimal loss at 6.43%, compared to the positive control.